Handke's «Kafkaesque» Novel: Semiotic Processes in Die Angst des Tormanns beim Elfmeter - June Schlueter (Studies in 20th & 21st Century Literature, 1979)
Die Angst des Tormanns beim Elfmeter is characterized by qualities which have come to be known as «Kafkaesque.» The behavior of the protagonist is unexplained, the prevailing atmosphere is one of anxiety, and a fuzzy suggestiveness informs the novel's fictive world. Yet, as with Kafka's work, mimetic or allegorical interpretations seem to impoverish rather than to enrich the text. It may well be that the primary concern of both authors is to illumine not the character of the world, but the character of meaning itself. In Handke's novel, Josef Bloch, eluding capture by the Austrian police following his murder of a movie clerk, engages in a search for «semiotic sanity». Bloch's exceptionally aware rethinking of relationship among the phenomenal world, self, and language yields considerable insight into the ontology of meaning, revealing the Kafkaesque qualities of the novel to be the product of normal semiotic processes of life.
Keywords: Die Angst des Tormanns beim Elfmeter; Kafkaesque; mimetic; allegorical; Handke; Josef Bloch; Austrian police; semiotic sanity; self; language